Amperometric Sensor for Detection of Chloride Ions - Trnkova, Libuse; Adam, Vojtech; Hubalek, Jaromir; Babula, Petr; Kizek, Rene (Sensors (Basel, Switzerland), 2008)
Chloride ion sensing is important in many fields such as clinical diagnosis, environmental monitoring and industrial applications. We have measured chloride ions at a carbon paste electrode (CPE) and at a CPE modified with solid AgNO₃, a solution of AgNO₃ and/or solid silver particles. Detection limits (3 S/N) for chloride ions were 100 μM, 100 μM and 10 μM for solid AgNO₃, solution of AgNO₃ and/or solid silver particles, respectively. The CPE modified with silver particles is the most sensitive to the presence chloride ions. After that we approached to the miniaturization of the whole electrochemical instrument. Measurements were carried out on miniaturized instrument consisting of a potentiostat with dimensions 35 × 166 × 125 mm, screen printed electrodes, a peristaltic pump and a PC with control software. Under the most suitable experimental conditions (Britton-Robinson buffer, pH 1.8 and working electrode potential 550 mV) we estimated the limit of detection (3 S/N) as 500 nM.
Keywords: Voltammetry; Screen Printed Electrode; Chloride Ions; Carbon Paste Electrode; Amperometry; Silver